In Vivo Endoscopic Tissue Identification by Rapid Evaporative Ionization Mass Spectrometry (REIMS). (14th September 2015) - Balog, Julia; Kumar, Sacheen; Alexander, James; Golf, Ottmar; Huang, Juzheng; Wiggins, Tom; Abbassi‐Ghadi, Nima; Enyedi, Attila; Kacska, Sandor; Kinross, James; Hanna, George B.; Nicholson, Jeremy K.; et al.
Abstract Gastrointestinal cancers are a leading cause of mortality, accounting for 23 % of cancer‐related deaths worldwide. In order to improve outcomes from these cancers, novel tissue characterization methods are needed to facilitate accurate diagnosis. Rapid evaporative ionization mass spectrometry (REIMS) is a technique developed for the in vivo classification of human tissue through mass spectrometric analysis of aerosols released during electrosurgical dissection. This ionization technique was further developed by utilizing surface induced dissociation and was integrated with an endoscopic polypectomy snare to allow in vivo analysis of the gastrointestinal tract. We tested the classification performance of this novel endoscopic REIMS method in vivo. It was shown to be capable of differentiating between healthy layers of the intestinal wall, cancer, and adenomatous polyps based on the REIMS fingerprint of each tissue type in vivo.